(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
The level of occupational respiratory diseases among workers in the mining, machine-building and metallurgical industries remains high. The most common occupational respiratory disease is pneumoconiosis, which is the result of the long-term inhalation of dust. It is possible to minimize the impact of dust on the workers and eliminate such diseases in the future due to the use of filtering mask respirators designed to reduce dust infiltration into the space under the mask. For this purpose, the choice of the type of elastic bands of filtering mask respirators has been substantiated by the geometric shape and tension forces that can ensure a permissible level of leakage of contaminated air into the breathing zone of the respirator during its use. A mathematical model has been developed to describe the influence of parameters of elastomeric headgear on the protective properties of the respirator. The dependence of the change in the residual tensile strength of the elastic bands of the headband has been established, and the dependence of the volume of air suction on the area of the elastic straps at the corresponding tension force has been determined. Using the model, the dependence of the volume of polluted air inflow on the area of the elastic straps at the corresponding tension force has been estimated. The design of the innovative inserts has been offered, which makes it possible to control the tension of the elastomeric head straps of the respirator to visualize the weakening of the pressure forces responsible for maintaining a tight fit.